Decentralized and concentrated investments in China and the performance of Taiwanese listed electronic companies - Wang W.-K.; Lu W.-M.; Kweh Q.L.; Liu Y.-L. (Routledge, 2023)
data envelopment analysis; decentralization; electronics industry; investment; operations technology; regression analysis; China